Urban underground space use in a climate neutral city - Bobylev, N.G.; Guo, D.; Benardos, A. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
Sustainable, compact, green and climate neutral urbanization is essential in the context of tackling global environmental challenges such as biodiversity conservation and climate change. Cities are expanding in both developed and developing countries; the rate of this growth is much higher than the growth of population. Responsible cities are pursuing a compact city policy, striving to exclude new construction in undeveloped and green areas. The three-dimensional development of cities, and the use of underground space in particular, is a complex, multidimensional and interdisciplinary task. Urban climate agenda widens the above research area further, requiring detailing climate adaptation and mitigation issues. The paper will present analysis of opportunities and drawbacks that the urban underground space brings to an urban transition towards climate neutrality. This research contributes to a vision for urban underground space and integrated urban planning that enhance the quality of urban life while pursuing climate responsible development agenda.